Presencia de Apimiasis (Diptera, Phoridae) asociada con una alta mortalidad de abejas africanizadas (Apis Mellifera l.) en la Zona de los Santos, Costa Rica - Calderón Fallas, Rafael Ángel (2006)
The occurrence of adult bee mostality infested with fly larvae on Africanized honey bee (AHB) colonies in Costa Rica, is reported. A comercial apiary of AHB colonies, located near Los Santos, province of San José, Central Vally of Costa Rica, was inspected in November 2002 (rainy season). Samples of crawling bees in front of the hive and dead bees were analyzed at the laboratry. About 80% of the adult bees in the samples were found to be infested by fly larvae in the thorax, black and humps backed adult flies in the broud nest of the colony, indicae that it belongs to tha Phoridae family, most likely Melaloncha sp.